The spatial reproduction number in a cellular automaton model for vector-borne diseases applied to the transmission of Chagas disease. (February 2016) - Cissé, Baki; El Yacoubi, Samira; Gourbière, Sébastien
This work aims at developing a general methodology to determine the spatial changes in the basic reproduction number for vector-borne diseases. This requires a spatially explicit modeling system which will be based on a cellular automata (CA) approach and applied to the Chagas disease for both homogeneous and heterogeneous landscapes. Using an extension of the so-called next-generation matrix, we obtained an expression for the basic reproduction numberR 0 that characterizes the spatial heterogeneity of the risk of emergence of an outbreak. The performed simulation with the built CA model shows the effect of local vector dispersal in a heterogeneous landscape for Chagas disease transmission.